Bed-days and costs associated with the inpatient burden of healthcare-associated infection in the UK. (August 2021) - Manoukian, S.; Stewart, S.; Graves, N.; Mason, H.; Robertson, C.; Kennedy, S.; Pan, J.; Kavanagh, K.; Haahr, L.; Adil, M.; Dancer, S.J.; Cook, B.; et al.
Summary: Background: Healthcare-associated infection (HAI) is associated with increased morbidity and mortality resulting in excess costs. Aim: To investigate the impact of all types of HAI on the inpatient cost of HAI using different approaches. Methods: The incidence, types of HAI, and excess length of stay were estimated using data collected as part of the Evaluation of Cost of Nosocomial Infection (ECONI) study. Scottish NHS reference costs were used to estimate unit costs for bed-days. Variable (cash) costs associated with infection prevention and control (IPC) measures and treatment were calculated for each HAI type and overall. The inpatient cost of HAI is presented in terms of bed-days lost, bed-day costs, and cash costs. Findings: In Scotland 58, 010 (95% confidence interval: 41, 730–74, 840) bed-days were estimated to be lost to HAI during 2018/19, costing £46.4 million (19m–129m). The total annual cost in the UK is estimated to be £774 million (328m–2, 192m). Bloodstream infection and pneumonia were the most costly HAI types per case. Cash costs are a small proportion of the total cost of HAI, contributing 2.4% of total costs. Conclusion: Reliable estimates of the cost burden of HAI management are important for assessing the cost-effectiveness of IPC programmes. This unique study presents robust economic data, demonstrating that HAI remains a burden to the UK NHS and bed-days capture the majority of inpatient costs. These findings can be used to inform the economic evaluation and decision analytic modelling of competing IPC programmes at local and national level.